Representations of Bosnia and Herzegovina in Hungarian Political and Popular Writings between 1878 and 1908: A Selected and Annotated Bibliography - Csiszár, Esztella (Context: Journal of Interdisciplinary Studies, 2022)
This selective annotated bibliography presents Hungarian texts published between 1878 and 1908 covering Bosnia and Herzegovina under the Austro-Hungarian occupation and annexation. It includes 100 entries of books, articles and pamphlets out of which 60 are annotated.The author categorizes the literature by broad themes such as political analyses and pamphlets, travel accounts, ethnographic/geographic studies and memoires of the occupation campaign, historiographies, and country profiles, information booklets, and provide descriptive annotations of representative articles in each category.